The Iraqi Journalistic Treatment of COVID-19 pandemic - Abbas, Ahmed Fadel; Ghintab, Azhar Sabeeh (ALBAHITH ALALAMI, 2023)
This research aims to investigate the approaches adopted by Iraqi newspapers in addressing the COVID-19 pandemic crisis. Employing a descriptive methodology and survey technique, the study conducts content analysis on articles published in three prominent newspapers: Al-Sabah, Al-Mada, and Tareeq Al-Shaab. A multi-stage sampling method was employed, encompassing 260 issues of the aforementioned newspapers. Data collection involved the use of a content analysis questionnaire, with the "How it was said?" method utilized to determine analysis categories. The results showed that Al-Sabah newspaper adopted a positive approach in addressing COVID-19-related topics, while Al-Mada newspaper remained neutral, and Tareeq Al-Shaab newspaper had a negative approach. Additionally, the study underscores a preference for internal sources and actors as primary information providers within the newspapers’ COVID-19 coverage. Based on these findings, it can be concluded that Al-Sabah newspaper took a positive stance towards the COVID-19 crisis, while Al-Mada remained neutral, and Tareeq Al-Shaab was negative in their treatment of these topics. The results indicate that the renowned trusted newspapers attached great importance to internal sources in their pandemic coverage.